Ebstein's anomaly repair in infant and adult: Report of two cases - Kabir, Jahangir; Rima, Rezoana; Khatoon, Soofia; Hassan, Rezaul; Hossain, Md. Zakir (Journal of Shaheed Suhrawardy Medical College, 2012)
Ebstein's anomaly (EA) is a rare but fascinating congenital heart disorder accounting for <1% of all congenital heart defects. It is a complex congenital anomaly with a broad pathologic-anatomical and clinical spectrum and no two patients are alike. Moderate to severe Ebstein's malformation remains a surgical challenge. We report our institutional experience with the surgical management of Ebstein's anomaly in a severely symptomatic four months old infant and a twenty year old grown up adult. The young infant with Ebstein's anomaly had severe tricuspid valve dysplasia, cyanosis, and gross cardiomegaly, hepatomegaly. Echocardiography severity score was 1.1 in infant (grade 3/4). Repair consisted of tricuspid valve repair, reduction annuloplasty, partial closure of atrial septal defect, and correction of all associated cardiac defects (PDA ligation).Adult Ebstein's anomaly patient underwent One and half ventricle repair which includes De-Vega repair of tricuspid valve, plication of atrialized RV , closure of ASD and a bidirectional Glenn shunt as part of the repair. The postoperative course was uneventful in adult patient except mild RV diastolic dysfunction. The infant required prolonged mechanical ventilatory support. She also developed lungs collapse-consolidation following extubation and septicaemia. At 2 years follow-up both patients showed improved exercise tolerance, infant showed significant weight gain. Echocardiographic studies reveal satisfactory monocusp valve function in both patients, with mild non- coaptation of the anterior leaflet and the septal structures with mild tricuspid valve regurgitation. Ebstein's repair has a good functional and hemodynamic outcome in infant and adult patients. One and one-half ventricular repair can be performed with an acceptable risk in adult and a biventricular repair is feasible and safe in a symptomatic infant. J Shaheed Suhrawardy Med Coll, 2011;3 (2): 48-52 DOI: http://dx.doi.org/10.3329/jssmc.v3i2.12079